The Off-Glide Sounds in Sarawak: A Regionally Sound Feature: (Bunyi Geluncuran di Sarawak: Suatu Ciri Bunyi yang Bersifat Wilayah) (Jurnal Bahasa, 2018)
This paper discusses the off-glide sounds which exist in the Malay dialect (Saribas, Krian, Rejang) as well as the Iban, Melanau and Bintulu languages. Since Iban language is the dominant language in Sarawak, and rich in glided sounds, a question arises as to whether they are influenced by the Iban language or caused by other factors. The discussion of this paper is based on Blust's (1997) on nasal and nasalization phenomenon in Borneo. Since the nasal preplosion is attested in several geographically discontinuous regions of Borneo, this linguistic characteristic seems to appear regionally rather than influenced by other languages. The linguistic features that are regionally characterized displayed two common phenomenon, namely: (1) its spread is geographically discontinuous, and (2) beyond a unitary language branch or language. In the Malay dialect of the Iban, Melanau and Bintulu languages examined here, the criteria correspond with the case of nasal preplosion as described by Blust. Additional data from Sumatera (Jambi Malay, Minangkabau and Kerinci), which are scattered outside the Borneo Island, also exhibited glided sounds at the end of words. Findings reveal that glided sounds in Sarawak native languages fulfilled both criteria, which is they contain this particular sound and by coincidence meet the criteria of Blust's framework.Keywords: off-glide sounds, regional, language influence, nasalisation